2015
DOI: 10.1002/2015ea000110
|View full text |Cite
|
Sign up to set email alerts
|

Influence of volcanic eruptions on midlatitude upper tropospheric aerosol and consequences for cirrus clouds

Abstract: The influence of downwelling stratospheric sulfurous aerosol on the UT (upper troposphere) aerosol concentrations and on cirrus clouds is investigated using CARIBIC (Civil Aircraft for Regular Investigation of the Atmosphere Based on an Instrument Container observations) (between 1999-2002 and 2005-2013) Due to consequent subsidence, the sulfur loading of the upper troposphere (S UT ) was increased by a factor of 2.5 compared to background levels. Comparison of S LMS and S UT during the seasons March-July a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 85 publications
2
21
0
Order By: Relevance
“…Gettelman et al () and Ghan et al () found similar‐magnitude effects of anthropogenic sulfur emissions on LW radiative forcing via aerosol modification of cirrus clouds in the Community Atmosphere Model version 5. At present there are no conclusive observations (Friberg et al, ; Luo et al, ; Sassen, ) to confirm or rule out the role of volcanic sulfuric acid particles in altering the properties of ice clouds. Moreover, the results from model studies that investigate the effects of either sulfate geoengineering or volcanic eruptions on the thermodynamic and microphysical properties of cirrus clouds remain equivocal, with the resulting changes in cloudiness, ice crystal number, and mass concentrations strongly depending on the freezing parameterization, the aerosol scheme used, and the aerosol size‐number distribution produced by an eruption (e.g., Cirisan et al, ; Jensen & Toon, ; Kuebbeler et al, ; Lohmann et al, ; Visioni et al, ).…”
Section: Resultsmentioning
confidence: 91%
“…Gettelman et al () and Ghan et al () found similar‐magnitude effects of anthropogenic sulfur emissions on LW radiative forcing via aerosol modification of cirrus clouds in the Community Atmosphere Model version 5. At present there are no conclusive observations (Friberg et al, ; Luo et al, ; Sassen, ) to confirm or rule out the role of volcanic sulfuric acid particles in altering the properties of ice clouds. Moreover, the results from model studies that investigate the effects of either sulfate geoengineering or volcanic eruptions on the thermodynamic and microphysical properties of cirrus clouds remain equivocal, with the resulting changes in cloudiness, ice crystal number, and mass concentrations strongly depending on the freezing parameterization, the aerosol scheme used, and the aerosol size‐number distribution produced by an eruption (e.g., Cirisan et al, ; Jensen & Toon, ; Kuebbeler et al, ; Lohmann et al, ; Visioni et al, ).…”
Section: Resultsmentioning
confidence: 91%
“…This relatively high depolarisation value suggests that particles in the layer were dominated by backscatter from ash rather than sulfate particles, although there was evidence of a greater backscatter by sulfate particles in the lower part of the layer. The observed mean particle depolarisation was generally higher than for the Kasatochi and Sarychev eruptions [28], less than for the Puyehue eruption [14,28] and much smaller than for the Eyjafjallajökull eruption in 2010 [68,69].…”
Section: Discussionmentioning
confidence: 67%
“…Shibata et al [68] observed liquid volcanic aerosols in association with tropical cirrus layers. Friberg et al [69] observed a decrease in mid-latitude cirrus cloud reflectance observed by satellite sensors following an increase in volcanic aerosol from several tropical eruptions. They suggested that the dimming was due to deactivation of the nuclei responsible for homogeneous freezing by the presence of volcanic sulfate aerosol.…”
Section: Synergy Of Lidar and Radiosonde Measurementsmentioning
confidence: 99%
“…This is in line with the previous finding of a strong influence of stratospheric aerosol on the extratropical UT aerosol. 11,46 Sulfate is the dominating form of the sulfurous aerosol in the atmosphere. 47,48 To further evaluate Fig.…”
Section: Resultsmentioning
confidence: 99%